Analisis Penggunaan Kaidah Al-Hajah Qad Tunazzalu Manzilah al-Darurah Dalam Fatwa Dewan Syariah Majelis Ulama Indonesia - MUSTOFA, IMAM (Universitas Islam Negeri Raden Intan Lampung, 2018)
The Fiqh Legal Maxim (al-qawā’id al-fiqhiyyah) or principles have an important role in facilitating the understanding of Islamic law. The Indonesian Ulama Council (MUI) as an authoritative institution that establishes fatwas based on the fiqh legal maxim. This paper reviewed and analyzed the intensity and accuracy of the use of legal maxim in the fatwa of the Sharia Council - Indonesian Ulama Council (DSN-MUI). The focus of the study in this paper was the principle of al-aḥājah qad tunazzalu manzilah al-darūrah, which is contained in the book collection of DSN-MUI fatwas on Islamic finance from 2000 to 2012. The study in this paper was based on literature data analyzed using content analysis method inductively. The analysis includes fatwa mapping, the intensity of the use fiqh legal maxim, and the accuracy of the use of principle. This study concluded that the fatwa of the Indonesian Sharia Council-Ulama Council regarding sharia finance from 2000 to 2012 frequently used the fiqh legal maxim of al-ḥājah qad tunazzalu manzilah al-ḍarūrah āmmah kanat aw khāṣṣah as a foundation. The high intensity of the use of this principle in the fatwa related to Islamic finance showed that this principle was considered vital in responding to community problems related to Islamic finance. The use of this principle by the DSN-MUI as the basis for establishing law in the fatwa related to the products and services of Islamic Financial Institutions (LKS) needed by the society is appropriate and can answer the problems of economic law in Indonesia.